Pengembangan Media Pembelajaran Accordion Book Berbasis Permainan JELITA Untuk Meningkatkan Minat Belajar Siswa Kelas IV Sekolah Dasar - Ni Komang Pande Tri Rahayu; I Nyoman Laba Jayanta; I Kadek Edi Yudiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
IPAS learning in elementary schools is still dominated by conventional methods with limited learning media, causing students to be passive and show low learning interest. This study aims to analyze the effectiveness of the JELITA game-based Accordion Book in improving fourth-grade students’ learning interest in Indonesian cultural heritage material. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The implementation used a one-group pretest–posttest design with 31 students. Data were collected through expert validation, learning interest questionnaires, and teacher and student responses. The results indicated that the media is highly valid (Aiken’s V = 0.97 for material experts and 0.96 for media experts), very practical (teacher response 100% and students 97%), and effective in improving learning interest. The mean score increased from 55.65 (pretest) to 93.81 (posttest), with Wilcoxon test significance of 0.000 (<0.05). Therefore, the JELITA game-based Accordion Book is appropriate as a concrete, interactive, and contextual IPAS learning media.